PKM. DI SMP DWIJENDRA BUALU DALAM PENGEMBANGAN EDPUZZLE DALAM MEDIA PEMBELAJARAN DARING - Orsidian Bili; I Made Surat (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2022)
Covid-19 is a dangerous disease. This disease could easily infect human. Therefore with the existence of Covid-19, the government enforce the regulation called PSBB (large scale of social distancing) to prevent the spread of Covid-19 virus in Indonesia. PSBB forces all outdoor activities to be stopped for a while, one of them is school activity, so children have to study from home via online. The application of online learning gives children a difficulty and bore them during the time of learning. This dedication aimed to effectify the use of Edpuzzle and WhatsApp during the pandemic, and also helped students to increase their motivations, therefore they will understand the subject. With Edpuzzle and WhatsApp, students will get knowledge and fun experience of learning in less than two months. videos on Edpuzzle and WhatsApp group discussion. Study the society to increase knowledge, insight, and motivation of learning during the pandemic.